2003
DOI: 10.1034/j.1399-3046.2003.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in pediatric transplantation: 2001 Annual Report of the North American Pediatric Renal Transplant Cooperative Study

Abstract: The North American Pediatric Renal Transplant Cooperative Study has collected clinical information on children undergoing a renal transplantation since 1987. This cooperative group now includes over 150 participating medical centers in the United States, Canada, Mexico, and Costa Rica. This report covers the years from 1987 through 2001 and includes data on 7545 renal transplants in 6878 patients. This report demonstrates changing trends in many areas of pediatric transplantation including increasing numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 11 publications
3
88
0
5
Order By: Relevance
“…Sustained proteinuria beyond 1 mo was identified in four patients, one of whom had donor pathology identified at the implantation biopsy, and two others had early acute rejection episodes. The 45% rate of treated hypertension at 1 yr was substantially lower than the 70% rate generally reported in pediatric renal transplant recipients (5).…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Sustained proteinuria beyond 1 mo was identified in four patients, one of whom had donor pathology identified at the implantation biopsy, and two others had early acute rejection episodes. The 45% rate of treated hypertension at 1 yr was substantially lower than the 70% rate generally reported in pediatric renal transplant recipients (5).…”
Section: Discussionmentioning
confidence: 47%
“…Much of the improvement in organ transplantation outcomes has been due to the prevention of early acute rejection episodes and prompt identification and treatment when they occur (5,(7)(8)(9). Whereas some single-center reports have described rates of acute rejection episodes as low as 13 to 26% at 1 yr in selected groups of pediatric recipients (10 -13), large multicenter studies have reported rates as high as 27 to 59% (14 -19).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the results of kidney transplantation in CNS are quite good and similar to those obtained in other etiologies. Patient survival at 5 years is over 90% and graft survival over 80% in registry databases and in single centers [40,41]. Chronic allograft nephropathy, however, is a major problem also in these patients, and a second transplantation is inevitable when the patients become young adults.…”
Section: Kidney Transplantationmentioning
confidence: 99%